2009
DOI: 10.1113/jphysiol.2009.172544
|View full text |Cite
|
Sign up to set email alerts
|

Myostatin represses physiological hypertrophy of the heart and excitation–contraction coupling

Abstract: Although myostatin negatively regulates skeletal muscle growth, its function in heart is virtually unknown. Herein we demonstrate that it inhibits basal and IGF-stimulated proliferation and differentiation and also modulates cardiac excitation-contraction (EC) coupling. Loss of myostatin induced eccentric hypertrophy and enhanced cardiac responsiveness to β-adrenergic stimulation in vivo. This was due to myostatin null ventricular myocytes having larger [Ca 2+ ] i transients and contractions and responding mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
71
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(79 citation statements)
references
References 50 publications
7
71
1
Order By: Relevance
“…More recent studies have further demonstrated myostatin inhibition of different cardiac muscle growth processes in vitro and in vivo (Shyu et al 2005, Morissette et al 2006, Artaza et al 2007, McKoy et al 2007, Rodgers et al 2009, Zhou et al 2010. It is surprising, therefore, that some studies have failed to identify cardiac hypertrophy in Mstn K/K mice (Morissette et al 2006, Cohn et al 2007, Heineke et al 2010 especially as overexpressing myostatin stimulates cardiac atrophy (Artaza et al 2007.…”
Section: Aging Mice Young Adultsmentioning
confidence: 99%
See 4 more Smart Citations
“…More recent studies have further demonstrated myostatin inhibition of different cardiac muscle growth processes in vitro and in vivo (Shyu et al 2005, Morissette et al 2006, Artaza et al 2007, McKoy et al 2007, Rodgers et al 2009, Zhou et al 2010. It is surprising, therefore, that some studies have failed to identify cardiac hypertrophy in Mstn K/K mice (Morissette et al 2006, Cohn et al 2007, Heineke et al 2010 especially as overexpressing myostatin stimulates cardiac atrophy (Artaza et al 2007.…”
Section: Aging Mice Young Adultsmentioning
confidence: 99%
“…We therefore performed DXA scans to assess body and bone composition and weighed individual muscles and organs from WT and Mstn K/K mice. We have previously reported that body and heart weights do not diverge until after w100 days (Rodgers et al 2009). It was therefore surprising to see that body weights were similar in aged WT and Mstn K/K mice ( Fig.…”
Section: Body Morphologymentioning
confidence: 99%
See 3 more Smart Citations